Miocene instead of Jurassic: the importance of sound fieldwork for paleontological data analysis. (March 2023) - Fürsich, Franz T.; Bhosale, Suraj; Alberti, Matthias; Pandey, Dhirendra K.
Abstract: A diverse molluscan assemblage dominated by turritellid gastropods found in Kachchh, western India, has been interpreted in the past as Late Jurassic (Oxfordian) in age, based on associated undoubtedly Oxfordian ammonites. Recently, several investigations focused on the assemblage dealing with taxonomic, paleoecological, and evolutionary aspects. An analysis of the associated bivalve fauna, foraminiferal assemblage, and the geological context strongly suggests a Miocene rather than a Jurassic age and invalidates several conclusions drawn from the alleged Jurassic age of the fossils.